Discrete element method simulation and experimental validation of particle damper system. Issue 4 (27th May 2014) - Lu, Zheng; Lu, Xilin; Jiang, Huanjun; F. Masri, Sami
Abstract : Purpose: – The particle damper is an efficient vibration control device and is widely used in engineering projects; however, the performance of such a system is very complicated and highly nonlinear. The purpose of this paper is to accurately simulate the particle damper system properly, and help to understand the underlying physical mechanics. Design/methodology/approach: – A high-fidelity simulation process is well established to account for all significant interactions among the particles and with the host structure system, including sliding friction, gravitational forces, and oblique impacts, based on the modified discrete element method. In this process, a suitable particle damper system is modeled, reaction forces between particle aggregates and the primary structure are incorporated, a reasonable contact force model and time step are determined, and an efficient contact detection algorithm is adopted. Findings: – The numerical results are further validated by both special computational tests and shaking table tests, with good agreements to the experimental results. The method is shown to be effective and accurate to simulate the particle damper system. Originality/value: – The approaches described in this paper provide an efficient numerical way to investigate complex particle damper systems.